Using Democracy and Its Development - Wiratno (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to explore the implementation of democracy and its development. The term democracy, when viewed from an etymological point of view, comes from the words demos (people) and cratein (to rule). Thus, democracy means government by the people, which in its further development, as we saw in the Declaration of Independence, is "of the people for the people and by the people". In other words, democracy means government from the people, for the people, and by the people. The development of a democratic government system does not only concern the political system but also the economy and global issues from only the political sphere to the sphere of social and economic life. Therefore, the discussion of the concepts of freedom and equality in democracy includes the concept of how democracy can be developed and practically can be realized. Although the democratic government system contains elements of strengths and weaknesses, it also contains weaknesses caused by, 1) In a democratic system where the majority wins, a compromise between several views is often sought. The weakness is that a compromise is difficult to find so the government is hampered in carrying out its duties; 2) It may occur that the resulting decision is not the best one, it may only be reached by an intermediate decision (mediocre); 3) Political figures can become thirsty for power and personal gain. This means they seek individual interests or group interests and the interests of the people are neglected; 4) In this democratic system each group (party) seeks as many supporters as possible to be able to influence government decisions. There can be fraud and intimidation to play a role in election campaigns. Even though there are weaknesses in the democratic system of government, this system must be rated as the best at this time. This is because, in a democratic system, the will of the people is obeyed as much as possible.